Analisis Employee Relations PT. Pertamina Patra Niaga Fuel Terminal (FT) Kotabaru Kalimantan Selatan - Nur, Maulidina Putri (PT Literasi Nusantara Publisher, 2023)
Communication activities in employee relations, aside from fostering a positive relationship between management and company employees, can also be directed towards motivating the employees. Employee relations assist in maintaining mutual understanding or cooperation between the organization and its public through communication channels both internally and externally. This research aims to investigate communication, team activities, commitment, well-being, and involvement at PT. Pertamina Patra Niaga FT Kotabaru. The research method employed is quantitative descriptive. Data collection technique utilized in this research is interviews. There are three informants in this study, namely the FT Kotabaru Supervisor, FT Kotabaru Supervisor's Secretary, and FT Kotabaru Sales Service Staff. The types and sources of data in this research are primary and secondary data. The research findings reveal that employee relations at PT. Pertamina Patra Niaga FT Kotabaru yield satisfactory and effective results. The employee relations conducted by PT. Pertamina Patra Niaga FT Kotabaru in South Kalimantan meet various components including communication, team activities, commitment, well-being, and involvement.